Development of Sustainable Tourism Destinations and Poverty Alleviation of Bangladesh (International Journal of Scientific Research and Management (IJSRM), 2020)
Tourism sector has been considered as the crucial sectors of many different countries of the world. And sustainable tourism brings enormous scope as a rapid growing economic sector on the basis of foreign exchange earnings and generation of employment opportunity and thereby elevating poverty from the country. The central aim of this study is to investigate the role of sustainable tourism in alleviating poverty from developing countries, especially the northern part of Bangladesh. For this purpose, the different tourism sites have been selected that are situated in Rajshahi region like Padma Garden, Varendra Museum and Shaheed Kamruzzaman Zoo. Rajshahi, the major tourist destination region in Bangladesh which is very beautiful and flourished that has a great chance to contribute country’s infrastructure and economic development. This study conducts a survey on 200 respondents in three different places of Rajshahi through the structured questionnaires, observation, interview and literature review. An exploratory research method was employed because the nature of the study was descriptive due to the fact that most of the respondents were illiterate or semi illiterate. Besides IBM SPSS Statistics 20 is being used to analyze the data. Through the factor analysis and other measurements tools this study expatiates the social, cultural, economic, environmental and other factors which touching the sustainability of Rajshahi and also provide recommendations about the required steps that needs to be taken into account to palliate and to manage the drawbacks of tourism to make Rajshahi as a sustainable tourism destination. Besides it reveals the relationship between tourism development and poverty alleviation in Bangladesh. The study also suggested few ways by which existing tourism can be promoted and well developed in Bangladesh thereby ensuring sustainable tourism development (STD) and economic growth.